2019
DOI: 10.1002/lary.28234
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of open bedside tracheotomy: A retrospective analysis of 1000 patients

Abstract: Objectives: To evaluate the safety/efficacy of performing open bedside tracheotomy (OBT) in intensive care unit (ICU) patients and identify predictive factors for outcomes.Methods: This is a retrospective cohort study. We identified 1000 consecutive patients undergoing OBT at a single university hospital starting from August 1, 2007. Complication rate, 30-day mortality, decannulation rate, time to surgery (TTS) from initial consult, and ICU length of stay were analyzed. Multivariate analysis was performed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 35 publications
4
31
2
Order By: Relevance
“…25,26 In a study by Liao et al, among 1,000 patients undergoing tracheotomies, the incidence of minor complications was 20% and the incidence of major complications were 1%. 15 We reported a minor complication rate of 9% and major complication rate of 9%. The slight increase in major complications in our study may be attributable to the effects of COVID-19 on the respiratory system as well as changes in surgical technique for COVID-19 patients.…”
Section: Tracheotomy Complicationsmentioning
confidence: 78%
“…25,26 In a study by Liao et al, among 1,000 patients undergoing tracheotomies, the incidence of minor complications was 20% and the incidence of major complications were 1%. 15 We reported a minor complication rate of 9% and major complication rate of 9%. The slight increase in major complications in our study may be attributable to the effects of COVID-19 on the respiratory system as well as changes in surgical technique for COVID-19 patients.…”
Section: Tracheotomy Complicationsmentioning
confidence: 78%
“…The observed pooled rate for decannulation in this study (34.9%) fits within the broad range of reported decannulation rates for critical care patients in the literature (16.7%-94%). 38-41 A recent study by Liao et al 39 observed a 16.7% decannulation rate in a consecutive series of 1000 ICU patients who underwent bedside tracheotomy, most commonly for prolonged intubation (96.6%), with an average time to decannulation of 40.9 days.…”
Section: Discussionmentioning
confidence: 99%
“…The observed pooled rate for decannulation in this study (34.9%) fits within the broad range of reported decannulation rates for critical care patients in the literature (16.7%-94%). [38][39][40][41] A recent study by Liao et al 39 observed a 16.7% decannulation rate in a consecutive series of 1000 ICU patients who underwent bedside tracheotomy, most commonly for prolonged intubation (96.6%), with an average time to decannulation of 40.9 days. While tracheotomy has not yet been demonstrated to provide a mortality benefit in patients with COVID-19, the well-known long-term sequelae of prolonged intubation have made it a necessary component of the management of patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, very high max-PEEP, comorbidity and sex were not associated with higher complication rates. In the literature, the association between comorbidity and the incidence of postoperative complications after tracheostomy is controversial: some Authors [19] didn't report any relationship, while others [20 , 21] described an association between obesity and late complications (airway stenosis), and between chronic hepatitis or platelet count and the risk of mortality. However, we must underline that the small sample size is a limit of this study, therefore we can't exclude that comorbidities or other variables could be associated with higher complication rates if the patients’ number was higher.…”
Section: Discussionmentioning
confidence: 99%